PENGARUH DIVIDEND PAYOUT RATIO, FIRM SIZE, DAN LEVERAGE TERHADAP VOLATILITAS HARGA SAHAM (Studi pada Perusahaan Indeks LQ-45 yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Oktavianti, Rika; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2020)
The study is aimed at analyzing the influence of Dividend Payout Ratio, Firm Size and, Leverage on Stock Price Volatility. The population in this study are companies listed in the LQ-45 Index on the Indonesia Stock Exchange for the period of 2016-2018. The data used are secondary data from Bloomberg and the Indonesia Stock Exchange Financial Reports that are published. Total companies that meet the criteria are 22 companies. The analysis technique used is linear regression analysis with the SPSS application program. The results showed that partially Leverage had a significant negative effect on Stock Price Volatility. Other variables, namely Dividend Payout Ratio and Firm Size do not significantly influence the Stock Price Volatility. Stimulously, Dividend Payout Ratio, Firm Size and Leverage have a significant effect on Stock Price Volatility. And based on the results of multiple analyzes, leverage is a variable that has a dominant influence on stock price volatility as indicated by the value of the beta coefficient (Î²) that is -0.040.